Surveillance for Hepatocellular Carcinoma: Current Best Practice and Future Direction - Kanwal, Fasiha; Singal, Amit G. (Gastroenterology (New York, N.Y. 1943), 2019)
Hepatocellular cancer (HCC) is the fourth leading cause of cancer-related deaths worldwide and the fastest growing cause of cancer deaths in the United States. The overall prognosis of HCC remains dismal, except for the subset of patients who are diagnosed at early stage and receive potentially curative therapies, such as surgical resection and liver transplantation. Given this, expert society guidelines recommend HCC surveillance every 6 months in at-risk individuals. Despite these recommendations, the effectiveness of HCC surveillance remains a subject of debate. We discuss current best practices for HCC surveillance and the evidence that support these recommendations. We also describe several initiatives that are underway to improve HCC surveillance and outline areas that may serve as high-yield targets for future research. Overall, we believe these efforts will help the field move toward precision surveillance, where surveillance tests and intervals are tailored to individual HCC risk. Doing so can maximize surveillance benefits, minimize surveillance harms, and optimize overall value for all patients.